Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.jid.2016.09.037
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Model of Atopic Dermatitis Biomarkers Highlights the Systemic Nature of the Disease

Abstract: Current atopic dermatitis (AD) models link epidermal abnormalities in lesional skin to cytokine activation. However, there is evolving evidence of systemic immune activation and detectable abnormalities in nonlesional skin. Because some of the best single correlations with severity (Scoring of AD, or SCORAD) are detected not only in lesional but also nonlesional skin and blood, more complex biomarker models of AD are needed. We thus performed extensive biomarker measures in these compartments using univariate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
168
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 171 publications
(186 citation statements)
references
References 61 publications
9
168
1
3
Order By: Relevance
“…However because of the heterogeneous nature of atopic dermatitis, the establishment of such correlations is complex. A recent study has suggested that the integration of biomarkers from lesional and nonlesional atopic dermatitis skin together to blood biomarkers gave the best correlation with atopic dermatitis severity measured by scoring atopic dermatitis (SCORAD) index score [9 ▪ ]. Another study found that a combination of four serum biomarkers: thymus and activation-regulated chemokine (TARC)/CC chemokine ligand 17 (CCL17), pulmonary and activation-regulated chemokine (PARC)/CC chemokine ligand 18 (CCL18), IL-22, and sIL-2R, correlated better with atopic dermatitis severity (six area six sign atopic dermatitis score) than individual biomarkers [10].…”
Section: Atopic Dermatitis Severitymentioning
confidence: 99%
“…However because of the heterogeneous nature of atopic dermatitis, the establishment of such correlations is complex. A recent study has suggested that the integration of biomarkers from lesional and nonlesional atopic dermatitis skin together to blood biomarkers gave the best correlation with atopic dermatitis severity measured by scoring atopic dermatitis (SCORAD) index score [9 ▪ ]. Another study found that a combination of four serum biomarkers: thymus and activation-regulated chemokine (TARC)/CC chemokine ligand 17 (CCL17), pulmonary and activation-regulated chemokine (PARC)/CC chemokine ligand 18 (CCL18), IL-22, and sIL-2R, correlated better with atopic dermatitis severity (six area six sign atopic dermatitis score) than individual biomarkers [10].…”
Section: Atopic Dermatitis Severitymentioning
confidence: 99%
“…Chemokine ligand‐2 represents a typical NF‐κB‐dependent inflammatory gene; CCL17 is secreted by epidermal keratinocytes and plays an important role in AD of humans and dogs . The primary keratinocyte cultures were transferred into 24 well plates (Thermo Fischer Scientific) at a density of approximately 1 × 10 5 /well and subcultured until 80% confluence in maintenance medium (10% FBS).…”
Section: Methodsmentioning
confidence: 99%
“…Both are characterized by cellular and molecular abnormalities, including markers of epidermal hyperplasia, cellular infiltrates and increased inflammatory mediators compared with skin from individuals without AD . The inflammatory changes evident in non‐lesional skin may reflect, in part, the systemic nature of AD …”
Section: Ad Pathophysiology: Complex Dysregulation Of Immune Pathwaysmentioning
confidence: 99%
“…Moderate‐to‐severe AD is viewed as a systemic disease with increases in T and B cells in the circulation as well as in skin tissue . The systemic nature of the disease is also reflected in associated comorbidities, including cardiovascular, neuropsychiatric and malignant diseases, among others …”
Section: Introductionmentioning
confidence: 99%